In silico analysis of luteolin derivatives as antibacterial agents targeting DNA gyrase and CTX-M-15 extended-spectrum β-lactamase of Escherichia coli - Nuzul Wahyuning Diyah; Dwi Ayu Indriani; Rachma Dessidianti; Siswandono Siswandono (Wolters Kluwer Medknow Publications, 2024)
Luteolin exhibited antibacterial activity against Escherichia coli and its chemical structure similar to that of ciprofloxacin (CPF) which works by inhibiting DNA gyrase. Filtrate from passion fruit extract containing luteolin and its derivatives could inhibit extended-spectrum β-lactamase (ESBL)-producing E. coli. Antibacterial compounds that can also inhibit ESBL will be valuable compounds to overcome the problem of resistant bacteria. This study aimed to ensure the potency of luteolin and luteolin derivatives targeting DNA gyrase and ESBL by in silico approach. Docking simulation of ligands L1-L14 was performed using AutoDock Vina, and pharmacokinetics and toxicity (absorption, distribution, metabolism, excretion, and toxicity) profiles were predicted by pKCSM online. The docking result revealed higher binding affinity on DNA gyrase (PDB.1KZN) of 12 luteolin derivatives (energy <−7.6 kcal/mol) compared to CPF and higher affinity (energy <−6.27 kcal/mol) of all compounds than clavulanic acid against ESBL CTX-M-15 (PDB.4HBU). The compounds could be absorbed through the human intestine moderately, which showed low permeability to blood-brain barrier, nontoxic and nonhepatotoxic. The most active luteolin glycoside (L6) is capable to inhibit DNA gyrase and ESBL from E. coli which provided the potential against resistant bacteria and was promoted as lead compounds to be developed further.